Inspired marketing the astonishing fun new way to create more profits for your business by following your heart - Vitale, Joe 1953- (John Wiley & Sons, 2008)
Praise for Inspired Marketing. "These days the competition is so fierce you have to do something new to get noticed and make sales. This is the most refreshing and engaging book I've seen to accomplish just that. Every page breathes stimulation and leads to inspiration. Get it. Read it. Live it."--Joseph Sugarman, President, BluBlocker Corporation. "Read this book and watch your fears dissolve, limitations evaporate, and the life of your dreams become your daily reality."-Ray Edwards, www.RayEdwards.com. "Inspired Marketing! is, quite simply, a lesson in life itself